Factors Affecting the Absenteeism Among Senior High School Learners - Cabrera, Bryan Axcel B.; Miranda, Blessie L.; Timtim, Steffanie T.; Dominado, Noel L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Student absenteeism was a persistent issue in education, affecting academic performance and future opportunities. This study explored the factors that influenced absenteeism among senior high school learners in one of the Public Secondary High Schools in Cluster 1 Division of Pampanga, Philippines. Using a sequential-explanatory research design, the study first collected quantitative data through surveys and then conducted qualitative interviews with selected respondents. Findings revealed that absenteeism was influenced by financial constraints, health issues, family problems, lack of sleep, overloaded academic activities, and unfavorable school environments. The study highlighted that student facing financial difficulties often missed school due to lack of transportation funds and daily allowances. Similarly, frequent illness and family-related responsibilities contributed to absences. Additionally, academic pressures, strict teachers, and peer conflicts negatively impacted students' motivation to attend school. The study emphasized the need for targeted interventions, such as financial aid programs, mental health support, and policy adjustments in school administration, to minimize absenteeism. Addressing these concerns could enhance student engagement, academic performance, and overall well-being